Efeito do uso da terra na qualidade da água de riachos neotropicais em múltiplas escalas espaciais. - Siqueira, Taís da Silva (2023)
Increased human activities are threatening watershed landscapes and water quality monitoring and multiscale analysis have become essential tools for water resource management. In order to evaluate the influence of land use on water quality at different spatial scales. Twelve low-order streams were selected in which limnological samplings (physical, chemical and biological) were carried out during the dry season. The water quality index was used, based on the quality standards of Canada and Brazil. The percentage of land use was measured at local scale and water network. The environmental variables were summarized through Principal Component Analysis (PCA) and subsequently used in the construction of Linear Models (lm) for each axis resulting from the PCA, using the percentage of land use classes and land slope. The presence of contamination by Lead, Chromium, Copper, Nitrogen and Escherichia coli was verified. It was found that the Canadian Water Quality Guidelines for the Protection of Aquatic Life (CWQG-PAL) were more effective in protecting aquatic ecosystems than the National Council for the Environment Resolution No. 357/2005 (CONAMA 357/2005), due to its constant, more rigorous and sensitive monitoring. Agricultural activities and those inherent to urban areas were the main responsible for the degradation of water quality. The negative impact of agriculture was observed both on a local scale and on the water network, while urban areas had a negative effect only on the water network scale. It was also found that forests on a local scale are associated with improved water quality. It emphasizes the importance of the multiscale approach in the management of watersheds and in public policies, which should consider not only forest preservation on a local scale, but also human activities throughout the watershed. It is recommended the need for a reformulation of CONAMA Resolution No. 357/2005 with a methodology applied to conservationism and holistic, as well as the importance of public policies and changes in the law of the Brazilian Forest Code on areas of permanent preservation.